Detecting coastal urbanization and land use change in Southern Turkey - Alphan, Hakan; Güvensoy, Laden (Journal of Environmental Engineering and Landscape Management, 2016)
One of the most important needs in contemporary landscape planning is quantitative land use/land cover (LU/LC) change information. The reason a strong emphasis is placed on landscape change information is that it serves as an ecological and geographical basis for preparing and implementing development plans in a more sustainable manner. Multi-temporal analysis of LU/LC changes on the Eastern Mediterranean coast of Turkey revealed that there is a marked preference for these areas primarily for building development. This paper demonstrates a methodology that relies on quantitative analysis techniques for assessing spatiotemporal changes in LU/LC in the case of the eastern Mediterranean coast of Turkey. In this respect, satellite image datasets (SPOT panchromatic, Landsat TM) acquired in 1989, 1995, 2001 and 2007 were enhanced. Resulting images were classified and compared to detect coastal urbanization and development trends. Post-classification change analyses were employed to quantify land cover conversions in three periods from 1985 to 1995, from 1995 to 2001 and from 2001 to 2007. This paper demonstrated that urban, agriculture and shrublands changed rapidly in this part of the Mediterranean coast.